Physical Activity Earlier in Life Is Inversely Associated With Insulin Resistance Among Adults in Japan - Hitomi Fujita; Akihiro Hosono; Kiyoshi Shibata; Shoko Tsujimura; Kyoko Oka; Naoko Okamoto; Mayumi Kamiya; Fumi Kondo; Ryozo Wakabayashi; Mari Ichikawa; Tamaki Yamada; Sadao Suzuki (Journal of Epidemiology, 2019)
Background: It is known that physical activity affects glucose metabolism. However, there have been no reports on the influence of physical activity earlier in life on subsequent glucose metabolism. Therefore, we analyzed the influence of physical activity in earlier decades of life on insulin resistance in middle aged and older residents in Japan. Methods: The subjects were 6,883 residents of Okazaki City between the ages of 40 and 79 years who underwent physical examinations at the Okazaki City Medical Association Public Health Center from April 2007 through August 2011. They gave informed consent for participation in the study. Data on individual characteristics were collected via a questionnaire and from the health examination records. Fasting blood glucose and insulin levels were used to calculate the homeostatic model assessment of insulin resistance (HOMA-IR). HOMA-IR >1.6 was considered to indicate insulin resistance for the purpose of logistic regression models. Results: The study sample included 3,683 men and 3,200 women for whom complete information was available. For those who exercised regularly throughout their teens to their 30s–40s, the odds ratio for having insulin resistance was 0.75 (95% confidence interval [CI], 0.58–0.96) for men and 0.76 (95% CI, 0.58–0.99) for women after adjusting for other variables, including age, body mass index, and present physical activity. A linear trend was also observed in both men and women. Conclusions: Subjects who have exercised regularly in the early decades of life are less likely to have insulin resistance later in life.